A photogrammetric method for calculating soil bulk density§. Issue 4 (6th May 2014) - Bauer, Thomas; Strauss, Peter; Murer, Erwin
Abstract: Soil bulk density is an important parameter in many research fields. Unfortunately, no single method exists for measuring bulk density for a wide range of soil conditions. We have carried out tests and compared the results of a photogrammetric method for bulk density estimation as a supplement to widely‐used methods (core method, excavation method).The differences between the methods indicate the potential for using photogrammetry as a supplementary application for estimating soil bulk density.